Cardiopulmonary Testing before Pediatric Adenotonsillectomy for Severe and Very Severe Obstructive Sleep Apnea Syndrome. (11th March 2021) - Clements, Anna Christina; Walsh, Jonathan M.; Dai, Xi; Skinner, Margaret L.; Sterni, Laura M.; Tunkel, David E.; Boss, Emily F.; Ryan, Marisa A.
Abstract : Objectives/Hypothesis: Adenotonsillectomy is first‐line treatment for pediatric obstructive sleep apnea syndrome (OSAS) when not otherwise contraindicated. There is concern severe OSAS increases risk of comorbid cardiopulmonary abnormalities, such as ventricular hypertrophy or pulmonary hypertension, which preoperative testing could detect. Our objective is to determine if there is a severity of pediatric OSAS where previously undetected cardiopulmonary comorbidities are likely. Study Design: Retrospective chart review. Methods: We performed a retrospective review of 358 patients ≤21 years with severe OSAS who underwent adenotonsillectomy at a tertiary hospital June 1, 2016 to June 1, 2018. We extracted demographics, comorbidities, polysomnography, and preoperative tests. Wilcoxon rank‐sum and logistic regression estimated associations of OSAS severity (based on obstructive apnea‐hypopnea index [OAHI], hypoxia, hypercarbia) with preoperative echocardiograms and chest X‐rays (CXRs). Results: Mean age was 5.9 (±3.6) years and 52% were male. Mean OAHI and oxygen saturation nadir were 30.3 (±23.8) and 80.7% (±9.2), respectively. OAHI ≥60 was associated with having a preoperative echocardiogram (OR, 3.8; 95% CI, 1.7–8.5) or CXR (OR, 3.0; 95% CI, 1.4–6.8) compared to OAHI 10–59. There were no significant associations between OSAS severity and test abnormalities. The presence of previously diagnosed cardiopulmonary comorbidities was associated with abnormalities on echocardiogram (OR, 36; 95% CI, 4.1–320.1) and CXR (OR, 4.1; 95% CI, 1.2–14.4). Conclusions: Although pediatric patients with very severe OSAS (OAHI ≥60) underwent more pre‐adenotonsillectomy cardiopulmonary tests, OSAS severity did not predict abnormal findings. Known cardiopulmonary comorbidities may be a better indication for cardiopulmonary testing than polysomnographic parameters, which could streamline pre‐adenotonsillectomy evaluation and reduce cost. Level of Evidence: 4 Laryngoscope, 131:2361–2368, 2021